Effect of biofilter storage density on the nutrient filtration capacity of Ulva lactuca (Research, Society and Development, 2022)
This work aimed to evaluate the filtering capacity of inorganic nitrogen and phosphorus by biofilter of the macroalgae Ulva lactuca as a function of stocking density in an AMTI system in water recirculation. The macroalgae were cultivated in 20 experimental units, with 5 stocking densities (2, 4, 6, 8 and 10 kg.m-3) and 4 replications. The concentrations of the nutrients ammonia (N-NH3), nitrite (N-NO2), nitrate (N-NO3) and phosphate (P-PO4) were analyzed at the time of interruption of supply (06:00) and after 12 hours (18:00) for evaluation of nutrient filtration. There were no significant variations (p>0.05) between the values ​​of filtration efficiency of nitrogen (EF-N) and phosphorus (EF-P) and of the filtration rate of nitrogen (TF-N) and phosphorus (TF- P) as a function of stocking density. However, an effect (p